High yielding rice variety SEBERI 3 for irrigated lowland rice production systems in Niger - CGIAR Research Program on Rice (2020)
An irrigated lowland rice variety, SEBERI 3 (TXD 88) was released in Niger in 2020 for irrigated lowlands after successful evaluation in multi-environment trials through the Africa-wide Rice Breeding Task Force.